Gender Representation in Education: Critical Discourse Analysis of Urdu Textbooks used in Primary Government Schools in Punjab - Munaza Hasan Nasir (PJE, 2023)
This research aims to explore the gender equality or lack thereof in the Urdu textbooks taught in Punjab, Pakistan. Gender bias in textbooks is an important but invisible and overlooked problem. Five Urdu textbooks taught in primary government schools in Punjab were selected for critical discourse analysis. Both qualitative and quantitative research methods were employed. The number of female and male characters, portrayal of domestic and professional roles by both genders, and cosmetic bias was taken into account.